STRATEGI KERJASAMA PERTAHANAN REPUBLIK INDONESIA DAN AMERIKA SERIKAT GUNA MENGHADAPI ANCAMAN KONFLIK LAUT CINA SELATAN DALAM RANGKA MENJAGA HAK BERDAULAT NKRI - Bambang Wasito; Surya Wiranto; Gentio Harsono (Institut Pendidikan Tapanuli Selatan, 2022)
The South China Sea (SCS) conflict was concern caused by national boundary and had potential natural resources. United States rejected China's disputed claims to offshore resources in July 2020 with increasing its exercises and patrols about freedom of navigation. Indonesia as Indo-Pacific region also deploys a geopolitical strategy with America order to maintain the country's sovereignty so that necessary to know the factors and strategies of defense cooperation between them two about SCS conflict. This is qualitative research with descriptive and ex post facto methods. Research data obtained by interview, observation and literature study. Validity of data was tested by triangulation method and analyzed accorded Hubberman and Saldana (2014)’s theory such as SWOT, PESTLE and AHP. The results show that strength of internal factors that can increase or hinder cooperation was existence of resource cooperation management agency (1.9). The weakness of internal factors was ego sectoral (1.89) but can be covered by strengths based on the IFAS matrix. The external factor that influences was free and active politics with an EFAS Matrix score of 4. The AHP calculation shows that the SO (Strengths-Opportuniny) strategy was the first ranks(0.50) such as Implementation of human resource management by maximizing capabilities of state institutions accordance with political culture, maximize institutional supervision and control based international issues as well as intensive cooperation and assessment.